Fetal pulmonary atresia with ventricular septal defect: Features, associations, and outcome in fetuses with different pulmonary circulation supply types. (12th August 2019) - Zhou, Jia; Zhou, Qichang; Peng, Qinghai; Zhang, Rongsheng; Tang, Wenjuan; Zeng, Shi
Abstract: Objectives: To assess features and outcome in fetuses with pulmonary atresia with ventricular septal defect (PA‐VSD). Methods: Fetuses with PA‐VSD were prospectively enrolled and grouped on the basis of the pulmonary blood supply, including type A (only arterial duct [DA]), type B (both DA and major aortopulmonary collateral arteries [MAPCAs] present), and type C (MAPCAs only). The echocardiography features, associated chromosomal/genetic malformations, and postnatal outcome were compared among the three groups. Results: Fifty‐five fetuses with PA‐VSD were enrolled. The presence of confluent PAs varied, with the highest displaying rate in type A and lowest rate in type C (100% vs 41.1%). The intrapericardial pulmonary arteries in all groups were hypoplastic but smaller in types B and C than in type A ( P < .05). Deletion of 22q11.2 and right aortic arch were more frequently observed in types B and C than in type A. At the end of the study, overall survival rates in type C were lower than those in type A (22.1% vs 77.3%). Conclusion: There are great differences in the size of pulmonary arteries, associated genetic malformations, and perinatal outcomes among fetuses with PA‐VSD. These results could be used for family counseling and surgical planning. Abstract : What's already known about this topic? Fetal echocardiography can be used to clarify the source of pulmonary blood supply and intrapericardial pulmonary arteries in fetuses with PA‐VSD. What does this study add? This study was designed to prospectively compare prenatal characteristics, associated genetic/structural abnormalities, and outcome in three types of fetuses with isolated PA‐VSD based on the source of pulmonary blood supply.